Resilient coping during the Russian-Ukrainian war: Does it buffer the effects of cumulative trauma on ICD-11 posttraumatic stress disorder symptoms? - Annett Lotzin; Olha Morozova-Larina; Antje Paetow; Lisa Schratz; Vladyslava Keller; Illia Zarubin; Liudmyla Krupelnytska (Comprehensive Psychiatry)
Background: Individuals with higher resilient coping may manage war-related trauma better than individuals with lower resilient coping. If so, resilient coping may weaken the relationship between war trauma and posttraumatic stress disorders. Objective: This study aimed to investigate the role of resilient coping in moderating the associations between cumulative war trauma exposure and ICD-11 posttraumatic stress disorders during war. Methods: This cross-sectional study included N = 851 Ukrainian students living in the Ukraine between December 2022 and January 2023 during the Russian-Ukrainian war. We tested a model in which resilient coping was specified as a moderator of the effect of war-related cumulative trauma exposure (Harvard Trauma Questionnaire-R) on ICD-11 posttraumatic stress disorder (PTSD), and disturbances in self-organization (DSO) symptom levels (International Trauma Questionnaire-R), respectively. We used Structural Equation Modeling and controlled our analysis for previous trauma exposure, gender, years of study, and level of income. Results: In contrast to our hypothesis, the level of resilient coping did not moderate the effect of cumulative war trauma exposure on PTSD and DSO symptom levels. Instead, we found a strong direct effect of the level of resilient coping on PTSD and DSO symptom levels. Conclusions: Resilient coping may directly affect the level of PTSD and DSO symptoms but may not weaken the association between trauma exposure and posttraumatic stress disorders during war.